Electoral engineering : voting rules and political behavior - Norris, Pippa (Comparative politics, political economy., 2004)
From Kosovo to Kabul, the last decade witnessed growing interest in 'electoral engineering'. Underlying the normative debates are important claims about the impact and consequences of electoral reform for political representation and voting behaviour. This study compares and evaluates two broad schools of thought.